Isolation and Characterization of Plasmid DNA in Streptococcus cremoris - Larsen, L. D. (1978)
Nine industrially important strains of Streptococcus cremoris (HP, AM(2), ML(1), WC, C(3), R(1), E(8), KH, and Wg(2)) were shown to possess a diversity of plasmid molecules. Molecular weights of plasmids were determined from their relative mobilities after agarose gel electrophoresis and via electron microscopy. To illustrate the varied plasmid sizes, strain HP contained plasmids of 26, 18, 8.5, 3.3, and 2 megadaltons (Mdal); strain ML(1) contained plasmids of 29, 18, 9, 4, 2.2, and 1.8 Mdal; and strain AM(2) had plasmids of 42, 27, 16, and 8.4 Mdal. The numbers of plasmids observed in the other strains were 6, 5, 5, 7, 5, and 4 for C(3), E(8), KH, R(1), WC, and Wg(2), respectively. A spontaneous proteinase-negative (Prt(−)) mutant of HP was missing the 8.5-Mdal plasmid, which suggests that in this strain proteinase activity could be linked to this particular plasmid. A lactose-negative (Lac(−)) Prt(−) mutant of ML(1) lacked the 2.2-Mdal plasmid. Under the conditions employed, antibiotic sensitivity and heavy-metal susceptibility did not correlate with the missing plasmid in Prt(−) HP or in the Lac(−) Prt(−) ML(1). Curing experiments with AM(2), using acridine dyes and elevated temperatures, did not yield Lac(−) variants. AM(2) was also cultured at high dilution rates in a chemostat for 168 h by using a buffered milk or lactic broth at 18 or 32°C with no selection of Lac(−) derivatives. The inability to obtain Lac(−) variants under conditions known to facilitate plasmid elimination suggests that lactose metabolism is not plasmid-mediated in AM(2).